2002
DOI: 10.1091/mbc.e02-02-0116
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Structural Requirement for Ergosterol in Long-chain Fatty Acid Synthesis Mutants Important for Maintaining Raft Domains in Yeast

Abstract: Fungal sphingolipids contain ceramide with a very-long-chain fatty acid (C26). To investigate the physiological significance of the C26-substitution on this lipid, we performed a screen for mutants that are synthetically lethal with ELO3. Elo3p is a component of the ER-associated fatty acid elongase and is required for the final elongation cycle to produce C26 from C22/C24 fatty acids. elo3⌬ mutant cells thus contain C22/C24-instead of the natural C26-substituted ceramide. We now report that under these condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
122
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 61 publications
7
122
0
Order By: Relevance
“…We became interested in the role of lipids in surface transport of Pma1 because we observed that Pma1 was rapidly degraded in cells that fail to elongate the ceramide-bound C22 fatty acid to the mature C26 very long-chain fatty acid, as is the case in cells lacking ELO3, a component of the ER localized acyl chain elongase [28,29]. Interestingly, this rapid turnover of Pma1 in the elo3D mutant correlates with a lack of the newly synthesized protein to acquire detergent resistance [29] (Fig.…”
Section: Coupling Of H D -Atpase Biogenesis To Sphingolipid Synthesismentioning
confidence: 99%
“…We became interested in the role of lipids in surface transport of Pma1 because we observed that Pma1 was rapidly degraded in cells that fail to elongate the ceramide-bound C22 fatty acid to the mature C26 very long-chain fatty acid, as is the case in cells lacking ELO3, a component of the ER localized acyl chain elongase [28,29]. Interestingly, this rapid turnover of Pma1 in the elo3D mutant correlates with a lack of the newly synthesized protein to acquire detergent resistance [29] (Fig.…”
Section: Coupling Of H D -Atpase Biogenesis To Sphingolipid Synthesismentioning
confidence: 99%
“…Evidence in the budding yeast, S. cerevisiae, suggests a genetic interaction between mutants in sterol and sphingolipid biosynthesis [4,5,29,30]. For example, mutants that affect the hydroxylation pattern of sphingolipids display synthetic growth defects with mutations in late-acting ergosterol biosynthetic genes [4].…”
Section: Systems-based Matchmakingmentioning
confidence: 99%
“…For example, mutants that affect the hydroxylation pattern of sphingolipids display synthetic growth defects with mutations in late-acting ergosterol biosynthetic genes [4]. By contrast, mutations that affect the synthesis of the sphingolipidspecific very-long chain C 26 fatty acid display strong synthetic lethality with mutations in ERG6, a methyltransferase that catalyzes the addition of a fungal-specific methyl group at position C 24 in the aliphatic side chain or ergosterol [5]. Figure 1 summarizes experimental evidence on genetic interactions between the sterol and sphingolipid synthetic genes.…”
Section: Systems-based Matchmakingmentioning
confidence: 99%
See 2 more Smart Citations